Mosby's critical care nursing reference - Stillwell, Susan B. (St. Louis, Missouri : Mosby Elsevier, 2002)
Provides information needed by the critical care nurse in a number of settings. This edition includes an introduction regarding the role, responsibilities, and routine of critical care nurses; information on pain, infection control, and cardiac surgery patients in the critical care unit; terminology, topics, modalities, and treatments.
Critical Care Patient Assessment Guides -- Acute Pain in the Critically Ill Patient -- Concepts Common in the Care of the Critically Ill Patient -- The Critically Ill Patient -- Psychosocial Concerns of the Critically Ill Patient -- Complementary Therapies -- Nursing Care of the Child in the Adult Intensive Care Unit (ICU) -- Monitoring the Critically Ill Patient -- Therapeutic Modalities -- Pharmacology in the Critically Ill Patient -- Scoring Tools -- Organ and Tissue Donation -- Body Surface Area (BSA) Nomogram -- Formulas -- Guides to Advanced Cardiovascular Life Support.
Includes bibliographical references and index.
Keywords: INTENSTIVE CARE NURSING -- HANDBOOKS, MANUALS, ETC